FLIPPED CLASSROOM AS LEARNERS’ AUTONOMY IN DEBATE COURSE - Khusnia, Aulia Nisa (PEOPLE: International Journal of Social Sciences, 2015)
A debate course is speaking class focusing on how students deliver their opinion on certain topics. The class is designed as a true debate competition. The challenges come when many topics need to be discussed. The teacher used a flipped classroom. It is a new pedagogical method employing a synchronous video lectures and practice problems as homework, and active, group based problems solving activities in the classroom. It represents a unique combination of learning. The steps for applying flipped classroom were: 1) The teacher divides students into 2 groups, affirmative and negative; 2) The teacher gives a certain topic to the groups; 3) the teacher asks the students to find articles related to the topic; 4) The teacher asks students to make a case building based on the topic. In conclusion, Students got benefits from the process of flipped classroom such as: 1) Students moved at their own pace; 2) Students did homework in different way; 3) Students got time to practice; 4) Students can use technology to support their learning; 5) Students force to learn inside and outside the class; 6) Students got their prior knowledge before coming to the class